Party Membership and Intra-Party Democracy: How Do Members React to Organizational Change within Political Parties? The Case of Belgium - Sandri, Giulia; Amjahad, Anissa (PARTECIPAZIONE E CONFLITTO, 2015)
Facing a crucial legitimacy crisis, many Western European political parties have recently undergone various forms of organizational changes by adopting procedures for increasing intra-democracy: internal ballots, internal referenda, primary elections and so on. Direct democracy is now used in a wide range of decision-making procedures such as candidate and leadership selection (Cross and Katz, 2013). These reforms have pro-vided new opportunities for participation to party members. What happens to more traditional elements of party internal structures when such instruments of intra-party democracy are adopted? And more specifically, how are such changes perceived by the party base? This paper explores the attitudes and behaviors of members with regard to intra-party democracy procedures. On the basis of a case study (Belgium) and of an original dataset, the paper explores the political consequences of intra-party democracy. We show that members’ satisfaction with the party and their degree of previous internal activism affect the level of involvement in intra-party democracy activities. However, the dissatisfaction of the party base vis-à-vis of the membership role is growing. Intra-party democratization seems to limit the organizational function of the grass-roots membership to a ‘cheerleading’ role.